What is the best pulse shape for pacing purposes? - Avinoam Rabinovitch; Doron Braunstein; Ella Smolik; Yaacov Biton; Revital Rabinovitch (Frontiers in Physiology)
IntroductionCell pacing is a fundamental procedure for generating action potentials (AP) in excitable tissues. Various pulse shapes have been proposed for this purpose, with the aim of either facilitating the achievement of the excitation threshold or minimizing energy delivery to the patient. This study seeks to identify the optimal pulse shape for each of these objectives.MethodsTo determine the most effective pulse forms, we employed a mathematical model simulating nonlinear tissue responses to a range of pulse shapes.ResultsOur results demonstrate that the rectangular pulse is optimal for reaching the excitation threshold, while the Gaussian pulse is superior in minimizing energy delivery. Other pulse shapes examined, including ramp-up, ramp-down, half-sine, and triangular (tent-like), fall between these two in terms of performance.DiscussionFrom a clinical perspective, the appropriate pulse shape should be selected based on the specific goal. For minimizing the pulse amplitude required to cross the excitation threshold, the rectangular pulse is recommended. In contrast, if reducing energy delivery to the patient is paramount, the Gaussian pulse is the preferred choice. In other scenarios, a judicious selection can be made based on the outcomes of our model and the clinical requirements.